Development of Qr Code Based Hidden Treasure Game Media on Akidah Akhlak Learning - Sheilla Fahira Khadna; Salminawati Salminawati; Zaini Dahlan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The objectives of this research include understanding the stage of development of media games hidden treasure-based joyful learning through the application QR Code Reader, the validity of the development of such media based on aspects of media, material, and language, the effectiveness of its use in increasing the interest and learning outcomes of students, as well as the practicality of the use of the media in the learning of Akidah Class VIII moral material against themselves. This research is research and development, which is a type of research that uses the research and development (R&D) method. The model development in this study uses the ADDIE development design model. The results of this study are that media, material, and language validators state that this media development is valid with the following percentage acquisitions: averaging 89,285% of which belongs to the category highly qualified; materially obtaining a percent of 95,652% of which falls into the category very qualified; and linguistically obtaining a percentage of 84,615% of which is in the category extremely qualified applied in the education of the ethics of the eighth grade. In terms of media effectiveness, the hidden treasure game results in increasing student interest in learning by combining the results of a limited trial and an extensive trial, resulting in an average N gain of 0.8113 with a high category, as well as 81% with a highly effective category, while the media efficiency of the Hidden Treasure game results in improving the learning results of students through combining limited test results and a wide trial, resulting in a mean N gain of 0.5641 with a moderate category and 56% with an effective category. The conclusion of this research is that the learning medium of the hidden treasure game is based on joyful learning through the application of QR Code Reader on the learning of Akidah Akhlak Grade VIII. The material of akhlak discharged itself as a valid and very practical learning medium to use as well as effective in improving the interests and learning outcomes of students.